ANALISIS DATA PETA KAPASITAS FISKAL DAERAH - Herdiyana, Deni (Jurnal Pajak dan Keuangan Negara (PKN), 2019)
The study was conducted to process and analyze the Regional Financial Ability (KKD) map data. The design of this research uses descriptive qualitative through desk study with a deepening of various laws and regulations and the processing of secondary data at the Directorate General of Fiscal Balance, Ministry of Finance.The results of the study concluded that the factors that most influenced the Regional Fiscal Capacity Map (KFD) for the provinces were PAD and DBH while for districts / cities were PAD, DAU, and DBH. In general, regions that have a high proportion of PAD / DBH to income have a high KFD Index, while regions with a low KFD Index generally have a low PAD. For provincial governments that have a low KFD Index, most (> 50%) districts / cities in their regions have a low KFD Index, while for provinces that have a high KFD Index, it does not necessarily mean that most districts / cities in the region have a high KFD Index.